Underdiversification in Private Companies: Required Returns and Incentive Effects - Elisabeth Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
Owners of private companies are often highly underdiversified which exposes them to idiosyncratic risk. We investigate the consequences of underdiversification at the company level. Information on US companies and their owners is obtained from the Survey of Consumer Finances and the Survey of Small Business Finances. Underdiversification, measured as the share of the owner's net worth invested in the company, has a significant positive relationship with profitability, measured as the return on equity. We identify two causes for this underdiversification effect: higher required returns and higher effort. The results have important consequences for investment decisions at private companies.
More recent version: http://hdl.handle.net/10419/29639
Keywords: G11; G32; 330; underdiversification; required returns; incentives; private companies; wealth; entrepreneurship; Klein- und Mittelunternehmen; Unternehmer; Investition; Portfolio-Management; Rentabilität; Ökonomischer Anreiz; Schätzung; Vereinigte Staaten